Pengaruh Free Cash Flow Dan Kualitas Audit Terhadap Manajemen Laba - Agustia, Dian (UNIVERSITAS NEGERI SURABAYA, 2013)
AbstractAsymmetric information refers to a situation where one party has more information than the other party. The agency problems arise from asymmetric information in the principal agent contracts. In addition, there are also several factors that could affect earnings management that is free cash flow and audit quality. The aim of this research is to provide empirical evidence about the impact of free cash flow and audit quality variables on discretionary accruals, as a measure of Earnings Management with the control variables company’s size. This research used 103 manufacturing companies listed in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2007-2011. Data were analyzed using multiple regression method. Based on the result of analysis concluced that the variable independent free cash flow have a negative and significant effect on earning management. It means that companies with high free cash flow will restrict the practice of earnings management. While the audit quality no significance effect on earning management.